Behavioral microstate analysis reveals gamma oscillations in BLA are associated with escaping-related context rather than threat itself - Han Hio-Been; Jisoo Kim; Cho Cheol Jun; Choi Ji Hyun (Jee H Choi) (한국뇌신경과학회, 2020)
(Intro) Basolateral complex of the amygdala (BLA) has been suggested to be a key player of fear perception in the mammalian brain. Yet BLA ensembles have been reported to exhibit gamma oscillations (30-70 Hz) under the various fear-related context (i.e., emotional arousal, anxiety) both in human and rodent brain, and their function remains largely unknown. (Methods) Here, we investigated BLA gamma dynamically changing throughout a robot predator attack within a naturalistic experimental setting, using CBRAIN (a platform of wireless neurotelemetry device with mobile edge computing). (Results) By classifying behavioral microstates of mice during the interactions with the robot predator in the sub-second timescale, we found that BLA gamma is closely related to escaping behaviors. Interestingly, BLA gamma was suppressed not only when the mouse is relatively safe but also when it gets focused attack from the predator. (Discussion) Our findings indicate the BLA gamma may encode upcoming threat which can be utilized to guide action that should be taken immediately, rather than the information of fear-related situation which is already happened.